2012
DOI: 10.1890/12-0567.1
|View full text |Cite
|
Sign up to set email alerts
|

Persistent carry‐over effects of planktonic exposure to ocean acidification in the Olympia oyster

Abstract: Predicting impacts of global environmental change is challenging due to the complex life cycles that characterize many terrestrial and aquatic taxa. Different life stages often interact with the physical environment in distinct ways, and a growing body of work suggests that stresses experienced during one life stage can "carry over" to influence subsequent stages. Assessments of population responses to environmental perturbation must therefore consider how effects might propagate across life-history transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
180
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(191 citation statements)
references
References 58 publications
10
180
1
Order By: Relevance
“…Work in three brooding Pocilloporids, however, revealed that larval size was positively related to survivorship (Isomura and Nishihira 2001), suggesting that carry-over effects from a small larval size such as those seen in our study could result in cascading consequences in future life stages. This is true in the case of the Olympia oyster, where exposure to ocean acidification during development resulted in smaller shell sizes, and the latent effect of small size persisted for more than a month in ambient common garden conditions (Hettinger et al, 2012). It appears for corals, however, that small size is not always a certain predictor of negative performance, as large and small larvae exposed to temperature and salinity stress had the same propensity for latent effects in the coral Orbicella faveolata (Hartmann et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Work in three brooding Pocilloporids, however, revealed that larval size was positively related to survivorship (Isomura and Nishihira 2001), suggesting that carry-over effects from a small larval size such as those seen in our study could result in cascading consequences in future life stages. This is true in the case of the Olympia oyster, where exposure to ocean acidification during development resulted in smaller shell sizes, and the latent effect of small size persisted for more than a month in ambient common garden conditions (Hettinger et al, 2012). It appears for corals, however, that small size is not always a certain predictor of negative performance, as large and small larvae exposed to temperature and salinity stress had the same propensity for latent effects in the coral Orbicella faveolata (Hartmann et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Oysters were raised through the larval phase and into early juvenile life at either an ambient partial pressure of carbon dioxide (pCO 2 ; targeted at 500 matm) or at an elevated level (targeted at 1000 matm; n ¼ 18 jars per level). The ambient level approximated a typical pCO 2 concentration that occurs presently during the summer months in Tomales Bay [18], whereas the elevated treatment was based on an increase of 500 matm, within the range of shifts predicted to occur by the end of this century [28]. The pCO 2 levels were established by filling the culture jars with FSW that had been held in 20 l carboys bubbled for 2-3 days with gas mixtures containing fixed CO 2 concentrations (traceable to the US National Institute of Standards and Technology).…”
Section: (B) Larval and Juvenile Prey Culturingmentioning
confidence: 99%
“…The pCO 2 levels were established by filling the culture jars with FSW that had been held in 20 l carboys bubbled for 2-3 days with gas mixtures containing fixed CO 2 concentrations (traceable to the US National Institute of Standards and Technology). To minimize off-gassing and maintain the desired pCO 2 within the culture jars, the same mixed gases were added continuously to the sealed air spaces over the jars (for additional description of the culturing system see [18]). Every other day, 90% of the seawater in each jar was removed via reverse-filtration through 125 mm mesh, and jars were refilled with carboy water pre-equilibrated to the appropriate pCO 2 level.…”
Section: (B) Larval and Juvenile Prey Culturingmentioning
confidence: 99%
“…Reduced sperm swimming speeds, together with smaller, fewer eggs, will reduce fertilization success (16). Studies of other stressors, such as ocean acidification, show that carryover effects in oyster larvae can persist through to later life, reducing settlement success, population growth, and productivity (17).…”
mentioning
confidence: 99%